(untitled) (Mustansiria Dental Journal, 2018)
Aim: To investigate whether mode of delivery is associated with mutans streptococci (MS) colonization and dental caries in pre school children. Methods: This study includes 64 pairs of mothers and their children aged 3- 5 years old (34 born vaginally and 30 born by Caesarean section).Data included a dental examination, a questionnaire survey of mode of delivery, maternal gestational age, as well as children’s birth –weight, and laboratory assessment (by collecting non stimulated saliva for each woman and child and homogenizing them then Mutans Streptococci (MS) were counted ,isolated, purified and diagnosed according to morphological characteristic . Results: Dental caries, salivary and plaque streptococcus mutans counts were significantly higher in children delivered by caesarean section mode than those delivered normally (P<0.05).There was a positive linear correlation between the mean value of DMFS, salivary and plaque streptococcus mutans count of children and their mothers, and this association statistically significant (P<0.05). Gender, gestational age and birth weight had no significant correlations with the dmfs of children (P>0.05). Conclusion: The mode of delivery is significantly correlated with MS colonization and caries outcomes in pre-school children.